PENGARUH METODE LEARNING STARTS WITH A QUESTIONS TERHADAP PENINGKATAN HASIL BELAJAR IPAS SISWA KELAS IV SD INPRES 3/77 BAJOE 1 - Sudarto, Sudarto; Sitti Rahmi; Aulia Firman (Jurnal Cakrawala Ilmiah, 2025)
This research is a pre-experimental research study aimed to determine whether the Learning Starts With A Question method has an effect on improving the IPAS learning outcomes of fourth-grade students at SD Inpres 3/77 Bajoe 1. The research design used is One-Group Pretest-Postest Design. The population in this study were all of the fourth-grade students of SD Inpres 3/77 Bajoe 1 with a sample of 19 students selected based on the saturated sample technique. The data obtained were then analyzed using a paired sample t-test with a significance level of 5%. From the results of the data analysis, it was obtained that tcount = 8.785> ttable = 2.100. So, t count> ttable then H0 is rejected which means that the IPAS learning outcomes before and after the implementation of the Learning Starts With A Question method differ significantly. Because the average IPAS learning outcomes of students after the implementation of the Learning Starts With A Question method are higher than before the implementation and the average is significantly different, it can be said that the Learning Starts With A Question method has a significant effect on improving the IPAS learning outcomes of students in grade IV of SD Inpres 3/77 Bajoe 1, Tanete Riattang Timur District, Bone Regency.